Study of Air-gap Magnetic Field & Characteristic Simulation for PMSM - LI Huaxiang; YUAN Yuepin (Kongzhi Yu Xinxi Jishu)
It presents a calculation method of PMSM characteristics. As a sample of PMSM for the 2004 Toyota Prius motor drive system, FEA method is used to calculate static air-gap magnetic field of the PMSM. It compares air-gap magnetic field distribution in the state without load and with load, confirms the fact that load air-gap magnetic field is dominated by stator current, and then simulate the characteristics of PMSM. According to that relative position of stator and rotor will affect output torque of motor, locked torque curve and electromagnetic torque curve in one cycle can be calculated by the FEA transient field method. After post-processing, we can draw a space-time vector graph of motor and can get other parameters. Simulation results show that this method can largely improve the calculation precision of characteristic & parameter of PMSM.